The influence of the crude oil and the gold on energy sector returns - Ekleysia Gracela Tanod; Florencia Arum Sari Pontoh; Gabril Tuyu; Halldila Marianne (Yayasan Widyantara Nawasena Raharja, 2022)
Oil and gold are the most essential commodities in the business world. During the Covid-19 pandemic, the price of gold tended to be stable and the price of crude oil, on the other hand, tended to increase. The objective of this study is to analyze the effect of crude oil returns and gold returns on the returns of firms especially in the energy sector during 8 June 2020 to 4 June 2021. This study finds that only crude oil returns significantly and positively impact the returns of the firms in the energy sector.